Home Advantage in Basketball: a Longitudinal Analysis of the NBA Playoffs (1946-2022) - Morgado, Gabriel [UNESP]; Barreira, Julia (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2023)
The aim of this study was to analyze the home advantage in the NBA playoffs from its first season, 1946/1947, to its most recent season, 2021/2022. All data was collected directly from the official NBA website. From each game we collected the season, name of the teams, final score, game location and playoff stage (first round, conference semi-finals, conference finals and finals). The home advantage was calculated as the number of home wins expressed as a percentage of all games played. We compare the HA between the seasons before and after 1965 using the Mann-Whitney test. The significance level was adopted at p < 0.05. From the analysis of 4,259 matches, we con-firmed the HA in NBA playoffs showing that approximately 65% of the games played at home correspond to victory. In 73 seasons (96%) the home teams had an advantage playing at home. Two seasons were exceptions, the 1965/66 and 2019/20, being the only ones in history in which the visiting teams had a great advantage during the playoffs. We found a decrease in HA after 1965 and a smaller variation among the seasons. Lastly, we found no difference among the playoff stages. These findings provide important information for coaches and manag-ers regarding the different strategies when playing at home or away during the NBA playoffs.
Keywords: performance; competitiveness; match location; team sport; crowd effect